Pengaruh Lingkungan Kerja dan Disiplin Kerja Terhadap Produktivitas Karyawan Pada Pabrik Gula Ngadiredjo Kediri - Mochamat Arif Andriansyah; Mahfudiyanto Mahfudiyanto (BIMA : Journal of Business and Innovation Management, 2019)
This research purpose to know influence of works environment and dicipline toward employee productivity in sugar company of Ngadiredjo Kediri. Technic data analysi kuantitatif in this research used with the collection the survey data or observasi using primary data who obtained by quesioners, this sample in this research amount 146 respondens. Take of sample by random sampling, that is taking of sample compound each subjects of the populations, therefore, all subjects was assumed same for every subjects to derive the occasion selected to be sample. Technic of analysis data used regresi linier berganda. The result of research is shown up that; 1) Working environment has influenced positive toward employees productivity, 2) working discipline has influenced significants for partial and simultaneous toward the employees of productivity, 3). Working environment and working discipline have influenced simultaneous toward employees productivity Sugar Company of Ngadiredjo Kediri.